Psychiatric disorders in chronic hemodialysis patients in a clinic in Bahia: the influence of the COVID-19 pandemic - Daniela de Queiroz Moura Landim; Melina Pinheiro Gomes de Souza; Lianna Gabriella Dantas; Ana Flávia Moura; José A. Moura-Neto; José Andrade Moura Júnior; Constança Margarida Sampaio Cruz (Brazilian Journal of Nephrology)
Abstract Introduction: Chronic Kidney Disease is associated, due to several factors linked to the disease, with a high rate of psychiatric disorders. With the COVID-19 pandemic, evidence suggests an increase in the already high prevalence of these disorders in chronic kidney patients. It is assumed that early diagnosis of psychiatric disorders can contribute to the development of treatment strategies, reducing the morbidity and mortality caused by the disorders. Objective: To determine the prevalence of psychiatric disorders in hemodialysis patients, evaluating the association of COVID-19 and some variables with the occurrence of these disorders. Methodology: Cross-sectional study carried out in a nephrology clinic in Bahia, in 2023. The sample consisted of 119 patients chosen by simple randomization. Patients were evaluated by the Mini International Neuropsychiatric Interview, an internationally validated interview. Results: Sixty-two patients (52.1%) had at least one psychiatric disorder. The most common were Generalized Anxiety Disorder (GAD) (42%) and Major Depressive Episode (MDE) (18.5%). There was no association between COVID-19 diagnosis and any psychiatric disorder. Among the 58 patients who had COVID-19, men had a lower chance of developing some disorder (OR = 0.30; 95% CI [0.10–0.91]), as did patients with >5 years of treatment (OR = 0.17; 95% CI [0.05–0.61]). Conclusions: The prevalence of psychiatric disorders is high. Among patients who had COVID-19, women had more psychiatric disorders, as well as, specifically, more GAD, and patients who had more than 5 years of treatment had a significantly lower chance of developing some psychiatric disorder.